Consumption Change‐Induced Transients in a Water Distribution Network: Laboratory Tests in a Looped System. Issue 10 (29th September 2022) - Meniconi, S.; Maietta, F.; Alvisi, S.; Capponi, C.; Marsili, V.; Franchini, M.; Brunone, B.
Abstract: At the Water Engineering Laboratory of the University of Perugia, Italy, a wide experimental program has been carried out in a polymeric pipe network with two 100 × 100 m square loops. The aim of this program is to analyze the dynamic response of the system to transients caused by a change in water consumption. To emphasize such a response, transients are generated by the complete and fast closure of an end‐user, located at the downstream end of a service line. During tests, the combined effect of simultaneous consumers, whose consumption is varied both deterministically and stochastically, has been analyzed. The tests allow examining the propagation of the generated pressure waves within the network for different water consumption variations and end‐user locations. The lessons learnt from the experimental results may help the water utility managers to identify the reasons for the higher frequency of occurrence and severity of faults in some specific portions of water distribution networks apparently "similar" to others where damages are less frequent and severe. Key Points: Several laboratory transient tests are carried out in a polymeric looped water distribution network (WDN) due to deterministic and stochastic consumption variations The results may help the water utilities to identify the reasons for the high occurrence and severity of faults in some portions of WDNs The reasons for faults may be repetitive and fast consumption changes, especially at night, and a high small‐diameter pipe percentage